2017
DOI: 10.1248/bpb.b17-00324
|View full text |Cite
|
Sign up to set email alerts
|

Echinocystic Acid Facilitates Neurite Outgrowth in Neuroblastoma Neuro2a Cells and Enhances Spatial Memory in Aged Mice

Abstract: Aging leads to functional changes in the brain and decreases ability of learning and memory. Neurite outgrowth is important in learning and memory, therefore regulation of neurite outgrowth might be a candidate for treating aged brain. Echinocystic acid (EA), a pentacyclic triterpene, has shown to exert various neurological effects. However, the effect of EA on neurite outgrowth has not been studied. In this study, we examined if EA is effective on neurite outgrowth and memory in aged mice. The effect of EA on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Over the past 2 decades, numerous studies have revealed the molecular mechanisms underlying the regulation of neurite outgrowth by various factors. The representative pathway for neurite outgrowth is the activation of the PI3K/Akt and/or protein kinase A (PKA)/mitogen-activated protein kinase (MAPK)/ERK signaling pathways [16,17,18,19,20,21]. We thus tested by immunoblot analysis whether compound 13 had the ability to promote the phosphorylation of ERK1/2 and/or Akt in neuro2a cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 2 decades, numerous studies have revealed the molecular mechanisms underlying the regulation of neurite outgrowth by various factors. The representative pathway for neurite outgrowth is the activation of the PI3K/Akt and/or protein kinase A (PKA)/mitogen-activated protein kinase (MAPK)/ERK signaling pathways [16,17,18,19,20,21]. We thus tested by immunoblot analysis whether compound 13 had the ability to promote the phosphorylation of ERK1/2 and/or Akt in neuro2a cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that compound 13 -induced neurite outgrowth from neuro2a cells was being regulated through the PI3K/Akt-mediated signaling pathway and not the PKA/MAPK/ERK one. Other various signal pathways such as c-jun N-terminal kinase (JNK) have been reported to be involved in neurite outgrowth of neuro2a cells [19,21]. We will investigate whether not only PI3K/Akt-mediated signaling pathway, but also other signaling pathway(s) underlie the compound 13 -induced neuronal differentiation or not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenoids, for example, ursolic acid, and echinocystic acid, are described to improve learning ability and memory in mice [ 274 , 275 ]. Ginsenoside Rg3 and Rh2 from red ginseng roots have a calming effect [ 276 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
“…Triterpenoids and triterpenoid-containing extracts stimulate expression and enhance enzymatic activity of pro-longevity proteins SIRT1, SIRT6, PGC-1α, and JNK [ 251 , 265 , 275 , 281 , 296 , 297 , 298 ]. Furthermore, in silico, in vitro, and in vivo experiments demonstrated that ursolic acid directly binds to the outer surface of mammalian SIRT1 [ 297 ], as well as links with nematode JNK-1 ATP-binding site [ 250 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%